Structural, morphological and temperature dependent electrical traits of Co0.9Zn0.1InxFe2-xO4 spinel nano-ferrites. Issue 21 (1st November 2021) - Rani, Ritu; Batoo, Khalid Mujasam; Sharma, Pankaj; Anand, Gagan; Kumar, Gagan; Bhardwaj, Sumit; Singh, M.
Abstract: An intensive research has been begun on spinel nano-ferrites owing to their unique and novel size dependent chemical and physical properties. Indium doped cobalt-zinc spinel nano-ferrites, Co0.9 Zn0.1 Inx Fe2-x O4 (x = 0.05, 0.1, 0.15, 0.2, 0.25, 0.3), have been fabricated through solution-combustion (SC) method and characterized for structural, morphological and temperature dependent electric and dielectric behavior. XRD affirmed that all spinel nano-ferrites have single phase. The TEM and EDX micrographs have confirmed morphology and composition of the samples, respectively. The crystallite size has decreased from 23.8 nm to 20.2 nm, while the lattice constant has been seen to enhance from 8.385 Å to 8.426 Å with the replacement of Fe 3+ ions by In 3+ ions. FTIR spectroscopy has been performed to extract the information about the stretching of metal-oxygen bonds as well presence of various functional groups. Moreover, FTIR has confirmed that there is no deviation in the structure of the Co–Zn spinel nano-ferrites with the addition of In 3+ ions. Additionally, there is no significant deviation in the peak positions of respective peaks has been observed except, when composition changes from x = 0.05 to x = 0.10 for peak I and peak II. The resistivity has been observed to decrease with the rise in temperature, which has confirmed the semiconductor character of the prepared spinel nano-ferrites. An enhancement in resistivity has been viewed with the rise in In 3+ ions, while a normal dispersion curve has been observed for the variation of the dielectric constant as a function of frequency. Spinel nano-ferrites show a decrease in the dielectric constant with the increase in frequency as well as indium ion content. The dielectric loss tangent shows minute values suggest the utility of the present spinel nano-ferrites for microwave frequency applications.